Dosmestikasi Ikan Gabus, Channa Striata Blkr, Upaya Optimalisasi Perairan Rawa di Provinsi Kalimantan Selatan - Untung Bijaksana (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Bijaksana, U. 2012.Â Snakehead Domestication, Channa Striata Blkr, Swamp Water Optimization Efforts in South Kalimantan Province. J. Lahan Suboptimal 1(1):92-101.This research aimed at domesticating snakehead in order to fulfill the consumption without relying on catch. This research was conducted in the Wet Laboratory of the Department of Aquaculture Faculty of Fisheries Banjarbaru from September to October 2006. Snakeheads caught in